Determinants of Safe Riding Behavior among Adolescent Motorcyclists in Urban Indonesia: A Cross-Sectional Study - Damayanti, Nadia Andina; Yulia, Yulia; Rahma, Gusni (JIK-JURNAL ILMU KESEHATAN, 2026)
Background: Traffic accidents are a leading cause of death among adolescents globally and nationally, with high school students in urban areas being particularly vulnerable due to high motorcycle usage and inadequate safety practices.Objective: This study aimed to analyze the factors associated with safe riding behavior specifically knowledge level, attitude, and riding equipment completeness among students of Senior High School X Padang in 2025.Methods: A quantitative cross-sectional study was conducted involving 95 students selected through purposive sampling. Data were collected via a validated and reliable online questionnaire administered through Google Forms on April 10–11, 2025. Univariate and bivariate analyses were performed using the chi-square test.Results: Among participants, 49.5% exhibited risky riding behavior, 31.6% had a low knowledge level, 41.1% held negative attitudes toward road safety, and 84.2% had incomplete riding equipment. Bivariate analysis revealed significant associations between knowledge level (p = 0.000) and attitude (p = 0.000) with safe riding behavior. No significant association was found between riding equipment completeness and safe riding behavior (p = 0.280).Conclusion: Knowledge and attitude are significant predictors of safe riding behavior among high school students. School-based interventions, including traffic safety education and attitude-change programs, combined with family and community involvement, are recommended to improve adolescent safe riding behavior.